PARAGANGLIOMA OF THE EXTERNAL AUDITORY MEATUS - Khan, Umar Daraz; Shah, Shabbir Hussain; Raziq, Fazle; Qayum, Iftikhar (Journal of Ayub Medical College Abbottabad, 2000)
Paragangliomas are uncommon tumors, with a presumed origin from 'glomus cells' at various places in the body. They have also been mistakenly labelled as Glomus Jugulare tumors. The actual origin from neural crest epithelium and its derivative structures is often difficult to judge from the histological appearance, as they appear more epithelial or "endothelial" in routine light microscopic sections. The higher resolution of the Electron Microscope as well as special stains for neuroepithelial products will generally resolve their nature in difficult cases. They are different from Chemodectomas with which they are often classified, as they do not show chromaffin activity, the hallmark of adrenal or extra-adrenal chromaffin tumors.